(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
The aim of this experimental work is to study the effect of nanoparticles added to diesel fuel on engine performance characteristic. Nano fuels are prepared by adding Al2O3 or TiO2, both with particle size less than 45nm of diesel fuel. Four doses of each type namely (25, 50, 100 and 150) ppm are prepared. These nanoparticles are blended with diesel fuel in varying volume fraction by the means of an electric mixer and an ultrasonicator. The Nano fuels are (DF+Al2O3) and (DF+TiO2). Physicochemical properties of nano fuels are measured and compared with these of neat diesel. The study shows that the addition of nanoparticles to diesel fuel improves its physical properties such as cetane number, thermal conductivity and viscosity. The influence of nanoparticles addition is very clear on the engine performance. The results show that the performance parameters are improved for example, brake thermal efficiency is increased from 19.4% for diesel to 21% and 25% for DF+Al2O3 and DF+TiO2 respectively, the brake specific fuel consumption (BSFC) is decreased by 8% and 20% for DF+Al2O3 and DF+TiO2 respectively, the brake specific energy consumption (BSFC) is decreased by 8% and 20% for DF+Al2O3 and DF+TiO2 respectively at 25ppm and 75% load. The exhaust gas temperature is 382°C for pure diesel while it is 417°C for DF+Al2O3 and 353°C for DF+TiO2. The peak pressure for pure diesel is 62 bar and it increases with DF+Al2O3 to 66.2 bar as for DF+TiO2 the peak pressure decreases to 57.2 bar at full load and 150ppm.